(untitled) - Miller, Kenneth S. (New York, 1957)
Outlines theory and techniques of calculus, emphasizing strong understanding of concepts, and the basic principles of analysis. Reviews elementary and intermediate calculus and features discussions of elementary-point set theory, and properties of continuous functions.
Keywords: Calculus,Tính toán